2016
DOI: 10.1021/acscatal.6b00393
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Ensemble of a TICT-AIEE Active Pyrazine Derivative and CuO NPs: A Potential Photocatalytic System for Sonogashira Couplings

Abstract: The donor–acceptor system 4 having pyrazine scaffold as an acceptor moiety coupled to donor amino groups through rotatable phenyl rings has been synthesized, which formed aggregates in aqueous media, exhibited copper induced restriction to intramolecular rotation, and served as a “not quenched” probe for the detection of copper­(II) ions. During this process, the aggregates of derivative 4 acted as reactors and stabilizers for the generation of CuO NPs and themselves became oxidized to form polyamine derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 69 publications
(60 reference statements)
1
25
0
1
Order By: Relevance
“…Heterogeneous catalysts are important owing to their recyclability and easy separation/recovery, especially in industrial applications. Recently, a few reports demonstrated the feasibility of photoinduced heterogeneous catalysis for Sonogashira cross‐coupling at room temperature, such as: a) using a supramolecular ensemble of a twisted intramolecular charge‐transfer states aggregation‐induced emission enhancement (TICT‐AIEE) active pyrazine and CuO nanoparticles (Scheme b); b) a silicon carbide‐supported Pd–Cu alloy (Pd 3 Cu 1 /SiC) or TiO 2 supported palladium NPs (Pd@TiO 2 ) (Scheme c); and c) TiO 2 ‐supported CuO bimetallic photocatalysts (Scheme d), for which cocatalysis of Ti to Cu ions is required for the coupling reactions to occur . Despite increased attention, most heterogeneous NP‐based catalysts still have some limitations.…”
Section: Methodssupporting
confidence: 87%
“…Heterogeneous catalysts are important owing to their recyclability and easy separation/recovery, especially in industrial applications. Recently, a few reports demonstrated the feasibility of photoinduced heterogeneous catalysis for Sonogashira cross‐coupling at room temperature, such as: a) using a supramolecular ensemble of a twisted intramolecular charge‐transfer states aggregation‐induced emission enhancement (TICT‐AIEE) active pyrazine and CuO nanoparticles (Scheme b); b) a silicon carbide‐supported Pd–Cu alloy (Pd 3 Cu 1 /SiC) or TiO 2 supported palladium NPs (Pd@TiO 2 ) (Scheme c); and c) TiO 2 ‐supported CuO bimetallic photocatalysts (Scheme d), for which cocatalysis of Ti to Cu ions is required for the coupling reactions to occur . Despite increased attention, most heterogeneous NP‐based catalysts still have some limitations.…”
Section: Methodssupporting
confidence: 87%
“…Thus,wedesigned and synthesized pyrazine derivative 1 which has l-alanine moieties as the chiral handle and amide linkages as binding units.Wechose pyrazine as ascaffold because of its known potential to form fluorescent aggregates through p-p intermolecular stacking and the hydrophobic effect in an aggregated state in aqueous media. [19] Derivative 1 undergoes self-assembly to generate fluorescent helical fibers in aqueous media and the alanine groups can transfer chirality in the aggregated state.T he as-prepared helical fibers exhibit as elective affinity towards Ni 2+ ions,a nd the co-assembly of helical fibers and Ni 2+ ions results in ac hirality transformation. Fortunately,c hirality inversion was accompanied by further aggregation of the helical fibers to generate as upercoiled 1:Ni 2+ ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…However, poor recyclability of this noble‐metal free photocatalyst for the Suzuki coupling reaction was found that the yield was decreased by 30 % after 4 recycles. Also, they prepared other noble‐metal free photocatalyst for visible light photocatalyzed Sonogashira C−C cross coupling . The photocatalyst was composed of TICT‐AIEE active pyrazine derivative and CuO nanoparticles, which exhibited excellent catalytic efficiency in Sonogashira couplings under mild conditions with a wide variety of substrates.…”
Section: Pd Free Photocatalysts For Visible‐light C−c Cross‐coupling mentioning
confidence: 99%